Metastasis of Laryngeal Squamous Cell Carcinoma to Bilateral Thigh Muscles. (14th December 2014) - Lucas, Zarah; Mukherjee, Akash; Chia, Stanley; Veytsman, Irina
Abstract : Importance . Laryngeal cancer infrequently results in distant metastases, but metastasis to skeletal muscle is extremely uncommon. Observations . A 55-year-old male presenting with progressive dyspnea and hoarseness was found to have Stage IVA T4aN2cM0 laryngeal cancer and eventually underwent total laryngectomy. Before the patient could be started on adjuvant chemoradiation, the patient developed masses on both thighs. Biopsy revealed metastatic squamous cell carcinoma consistent with the primary laryngeal cancer. He was offered palliative chemotherapy; however, he developed new soft tissue masses to the left of his stoma and in the prevertebral area one week later. He also had new cervical and supraclavicular nodes and a pathological compression fracture of L3. Patient died within 4 months of diagnosis. Conclusions . Distant metastasis such as skeletal metastasis portends a poor prognosis. Further studies are required to determine the best course of treatment in these patients.